2016
DOI: 10.1111/ejn.13483
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo effects of a novel dimeric inhibitor of PSD‐95 on excitotoxicity and functional recovery after experimental traumatic brain injury

Abstract: PSD-95 inhibitors have been shown to be neuroprotective in stroke, but have only to a very limited extent been evaluated in the treatment of traumatic brain injury (TBI) that has pathophysiological mechanisms in common with stroke. The aims of the current study were to assess the effects of a novel dimeric inhibitor of PSD-95, UCCB01-147, on histopathology and long-term cognitive outcome after controlled cortical impact (CCI) in rats. As excitotoxic cell death is thought to be a prominent part of the pathophys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 99 publications
0
9
0
Order By: Relevance
“…Therefore, the interaction between glutamate receptors and postsynaptic scaffold proteins contributes to the modulation of neuronal injury after TBI. Disruption of the interaction between PSD-95 and NR2B, a NMDAR subunit, reduced brain damage and improved neurological dysfunction after TBI 4,10 . Furthermore, Homer 1a attenuated neuronal injury and brain damage after TBI by differentially regulating group I mGluRs 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the interaction between glutamate receptors and postsynaptic scaffold proteins contributes to the modulation of neuronal injury after TBI. Disruption of the interaction between PSD-95 and NR2B, a NMDAR subunit, reduced brain damage and improved neurological dysfunction after TBI 4,10 . Furthermore, Homer 1a attenuated neuronal injury and brain damage after TBI by differentially regulating group I mGluRs 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The postsynaptic density-95 (PSD-95) protein is another important postsynaptic scaffold protein that binds NR2B, a subunit of NMDAR, together with neuronal nitric oxide synthase (nNOS). Recently, pharmacological inhibitors that uncouple PSD-95 from NMDAR signaling have been shown to reduce trauma-induced brain damage and neurological deficits 4 . These results indicated that postsynaptic scaffold proteins are potentially valuable for investigating the mechanism underlying the pathogenesis of TBI and potential targets for TBI interference.…”
Section: Introductionmentioning
confidence: 99%
“…Further, a rodent model of CCI showed loss of PSD-95 with loss of neuronal NeuN in contused cortex and directly correlated with behavioral abnormalities [ 64 ]. UCCB01-147 [also known as Tat-NPEG4(IETDV)(2), (Tat-N-dimer)], a dimeric PSD-95 inhibitor, was observed to be neuroprotective in an experimental stroke model [ 65 ] but failed to demonstrate those beneficial effects in experimental TBI [ 66 ]. Therefore, it can be argued that PSD-95 alone or with other effector proteins may provide a potential clinical therapeutic target to improve memory and learning deficits but must be translated carefully for better results post-TBI.…”
Section: Excitotoxicitymentioning
confidence: 99%
“…Prior studies with retrograde dyes and 2D imaging approaches have cataloged mouse supraspinal populations (Liang et al, 2012b(Liang et al, , 2011; the 3D approach now offers a means to place these populations into spatial context while accelerating the task of surveying populations globally. For example, in experimental brain syndromes such as stroke, traumatic brain injury and genetic diseases that involve descending motor pathways, this approach could clarify when and where axonal abnormalities originate, while quantifying in an unbiased way neurons that maintain intact connections (Carron et al, 2016;Sommer et al, 2017). Variable sparing of axons often complicates spinal injury experiments, and thus one application of this technique would be to immediately supply AAV2-Retro distal to injury site, followed by 3D imaging throughout the brain to rapidly quantify the distribution of virally labeled (spared) axons and neurons.…”
Section: Aav2-retro and 3d Microscopy As A Tool For Functional Neuroamentioning
confidence: 99%